2019
DOI: 10.3389/fevo.2019.00322
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent With Parents Varies With Early-Life Condition, but Does Not Predict Survival or Sociality of Juvenile Hihi

Abstract: Many young birds die soon after fledging, as they lack the skills to find food and avoid predation. Post-fledging parental care is assumed to assist acquisition of these vital skills. However, we still lack empirical examples examining the length of time fledglings spend with parents, how they associate during this critical time, or whether such variation in the fledgling dependency period has consequences for the survival and behaviour of young as they navigate their first year of independent life. Here, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Individuals sharing an important part of their home-range are more likely to interact with each other than with non-neighbouring individuals. Copying other individuals' behaviour is frequently observed in wild animal populations (Dugatkin 1996;Laland 2004), including the hihi (Franks and Thorogood 2018;Franks et al 2019), and can result in the rapid spread of specific behavioural phenotypes, ultimately increasing behavioural heterogeneity between groups. For example, variation in behaviour can be observed locally for traits such as foraging (Coolen et al, 2003), parental care (Champagne, 2008), mate and habitat choice (Dugatkin 1996;Doligez et al 2002) or predator evasion (Halloy et al 2007).…”
Section: Dissecting the Spatial Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals sharing an important part of their home-range are more likely to interact with each other than with non-neighbouring individuals. Copying other individuals' behaviour is frequently observed in wild animal populations (Dugatkin 1996;Laland 2004), including the hihi (Franks and Thorogood 2018;Franks et al 2019), and can result in the rapid spread of specific behavioural phenotypes, ultimately increasing behavioural heterogeneity between groups. For example, variation in behaviour can be observed locally for traits such as foraging (Coolen et al, 2003), parental care (Champagne, 2008), mate and habitat choice (Dugatkin 1996;Doligez et al 2002) or predator evasion (Halloy et al 2007).…”
Section: Dissecting the Spatial Matrixmentioning
confidence: 99%
“…Zealandia sanctuary shelters a highly heterogeneous landscape composed of intact native bush, planted exotic trees and regenerating forest patches (Starbridge 2009). Previous quantitative genetic studies on another hihi population have demonstrated low narrow-sense heritability for morphological and life history traits despite large phenotypic variation between birds (de Villemereuil et al, 2018a;de Villemereuil et al, 2019), reinforcing the need to explore other forces generating differences between individuals such as the influence of the spatial structure of the population (Franks et al 2019). First, we studied dispersal patterns of hihi across Zealandia's landscape in order to understand how birds establish their home-range.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these findings indicate that young passerines may not retain specific preferences from early-life exposure to stimuli with parents. This could be due to the short period of dependency found in many Passeridae (for example, hihi spend approximately two weeks in the natal territory [51]) in comparison to other species which have longer post-fledging association with parents (e.g. : [17]).…”
Section: Discussionmentioning
confidence: 99%